Characterisation and in silico evaluation of secondary metabolites reported in Nyctanthes arbor-tristis L. with anti-arthritic properties - Padmavathi, T V S; Amrutha, V A (Plant Science Today, 2026)
The current study made an attempt to explore bioactive secondary metabolites as an alternative or complementary source for the treatment of rheumatoid arthritis. It aimed at the characterization of secondary metabolites present in methanolic leaf extract of Nyctanthes arbor-tristis (MLEN) having anti-arthritic properties using thin layer chromatography (TLC), high-performance liquid chromatography (HPLC) and nuclear magnetic resonance (NMR). Further, in silico evaluation of bioactive principles was performed against rheumatoid arthritis factors visfatin, resistin, chemerin, leptin, adiponectin and lipocalin 2 using AutoDock Vina. Two colour bands with Rf values of 0.44 and 0.88 were resolved with the mobile phase of n-butanol: acetic acid: water (50:10:40) in TLC. HPLC metabolite profiling and 1H and 13C NMR spectroscopic analyses reported a total of eleven phenolic compounds (gallic acid, syringic acid, ferulic acid, luteolin, benzoic acid, kaempferol, ellagic acid, chrysin, phenylacetic acid, chlorogenic acid and p-coumaric acid) with luteolin being most abundant (73 µg/mL). Through in silico evaluation, the identified compounds have shown favourable binding affinities with the targets. Chlorogenic acid has shown the highest binding affinity of -10.2 kcal/mol with visfatin (PDB ID 5LX5), -8.2 kcal/mol with chemerin (PDB ID 7YKD) and -7.8 kcal/mol with resistin (PDB ID 1RFX) confirming its strong affinity to inhibit inflammation due to arthritis. These findings infer that MLEN has promising anti-arthritic activity. Further research in the field of in vitro and in vivo anti-arthritic activity, followed by toxicity parameters, may authenticate the therapeutic potential of the extract in the treatment of arthritis.